2022
DOI: 10.1186/s40462-022-00301-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of wind in controlling the connectivity of blue mussels (Mytilus edulis L.) populations

Abstract: Background Larval connectivity between distinct benthic populations is essential for their persistence. Although connectivity is difficult to measure in situ, it can be predicted via models that simulate biophysical interactions between larval behaviour and ocean currents. The blue mussel (Mytilus Edulis L.) is widespread throughout the northern hemisphere and extensively commercialised worldwide. In the Irish Sea, this industry represents ~ 50% of Welsh shellfisheries, where cultivation is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Previous studies have shown the importance of circulation patterns on interannual variability of larval recruitment and dispersal (McQuaid and Phillips, 2000;Largier, 2003), and interactions between larval vertical migration and stratification have been shown to be an important driver of dispersal (Raby et al, 1994). Moreover, the water column in the West coast of Scotland remains well mixed since winter until May, which implies that stratification might not play a role in earlier spring on larval dispersal, as also shown in Figure 4; this is in addition supported by Demmer et al (2022) for the study of mussel dispersion in the northern Irish Sea.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies have shown the importance of circulation patterns on interannual variability of larval recruitment and dispersal (McQuaid and Phillips, 2000;Largier, 2003), and interactions between larval vertical migration and stratification have been shown to be an important driver of dispersal (Raby et al, 1994). Moreover, the water column in the West coast of Scotland remains well mixed since winter until May, which implies that stratification might not play a role in earlier spring on larval dispersal, as also shown in Figure 4; this is in addition supported by Demmer et al (2022) for the study of mussel dispersion in the northern Irish Sea.…”
Section: Discussionsupporting
confidence: 73%
“…Our results show that there is no significant difference in dispersal patterns between the three depths tested by the model. Indeed, assuming that larvae are distributed throughout the water column, performing only a limited vertical migration and in the absence of stratification, then their dispersal would be primarily controlled by tidal currents (Raby et al, 1994;McQuaid and Phillips, 2000;Demmer et al, 2022). Furthermore, assuming that bivalve larvae are mainly distributed in the near-surface waters, their dispersal would additionally be influenced by wind-driven currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data was used in several ways, (1) to extract the data pertaining to that of the pelagic larval phase per season (December to February-summer; March to May-Autumn; June to August-Winter; September to November-Spring), (2) to track the movement of the particles which could then provide details of the approximate number of generations needed for connectivity among dispersed locations, and (3) enumerating connectivity by calculating the total number of particles arriving at each SCI sample area from each source sample area over the modelling period (i.e., source-sink dynamics). Our use of hydrodynamic models for simulating larval dispersal draws on well-established research for a wide range of marine species e.g., [109][110][111][112] . However, our approach to the application of the modelling differs in that we are interested in multigenerational connectivity which is consistent with the biological process for migration of genes within a wide ranging population, and it ensured that inter-annual variability in hydrodynamic processes were incorporated into the modelled outcomes, whilst also ensuring there was enough time for particle dispersal to assess possible long distance multigenerational dispersal.…”
Section: Gbs Sample Preparationmentioning
confidence: 99%
“…Following the construction of OWFs, the presence of hard substrates and foundations attracts various benthic species, predominantly dominated by the presence of mussels, as highlighted by the authors of [16]. The establishment of offshore wind farms, recognized as stepping stones, has facilitated the broader dispersal of mussels (Mytilus edulis) in the North Sea [17][18][19][20]. Simultaneously, in the English Channel, prior to the implementation of wind farms, natural larval dispersion has been modeled.…”
Section: Introductionmentioning
confidence: 99%